A food spectrum analysis of three bufonid species (Anura: Bufonidae) from Uttarakhand region of the western Himalaya, India - Vivekanand Bahuguna; Ashish Kumar Chowdhary; Shurveer Singh; Gaurav Bhatt; Siddhant Bhardwaj; Nikita Lohani; Satyanand Bahuguna (Journal of Threatened Taxa, 2019)
The ecological diversity of insects and its predators like amphibians are important determinants in ecological balance.  A total of 1,222 prey items in 84 specimens were examined to contribute the understanding of the diets of three Duttaphrynus species, viz., himalayanus, melanostictus, and stomaticus from Uttarakhand, the western Himalaya, India.  Gut content analysis of three bufonids revealed acceptance of a wide range of terrestrial insects and other invertebrates as their food.  The index of relative importance indicated that the most important preys were Formicidae, Coleoptera and Orthoptera.  Duttaphrynus melanostictus had the broadest dietary niche breadth, followed by D. himalaynus and D. stomaticus.  The wide prey spectrum well indicates that these species are the generalist and opportunist invertebrate feeder.  Information pertaining to the food spectrum analysis contributes to understanding the ecological roles and used as a baseline data for future successful amphibian conservation and management programs in the Himalayan ecosystem.